2016
DOI: 10.1007/s00280-016-3228-y
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of lenalidomide in multiple myeloma patients

Abstract: This study identified creatinine clearance and body surface area as covariates that have a clinically relevant impact on lenalidomide pharmacokinetics using population pharmacokinetics. In addition, the developed population pharmacokinetic model can be used to individualize lenalidomide dose in multiple myeloma patients, taking into account not only creatinine clearance but also body surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…A population PK model, previously developed using data from daratumumab monotherapy studies [ 14 ], was used to fit concentration–time data from the four combination studies. No direct impact of the background therapies on the PK of daratumumab was expected given the lack of overlapping clearance mechanisms for daratumumab and the co-administered small-molecule therapies [ 22 24 ]. NONMEM ® 7.2 software (ICON, Dublin, Ireland) was used for population PK modeling.…”
Section: Methodsmentioning
confidence: 99%
“…A population PK model, previously developed using data from daratumumab monotherapy studies [ 14 ], was used to fit concentration–time data from the four combination studies. No direct impact of the background therapies on the PK of daratumumab was expected given the lack of overlapping clearance mechanisms for daratumumab and the co-administered small-molecule therapies [ 22 24 ]. NONMEM ® 7.2 software (ICON, Dublin, Ireland) was used for population PK modeling.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent population‐pharmacokinetic study, it was shown that lenalidomide exposure was dependent not only on the renal function but also on the body‐surface area (BSA). The authors suggested that BSA should be taken into account in the dosing adjustment in advance to prevent toxicity.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…In this preliminary analysis, creatinine clearance (CrCl), a marker of renal function, was the only significant covariate of lenalidomide apparent clearance, and no differences in PK were observed among MM, MCL, and MDS patients . Recently, the PopPK of lenalidomide was explored in a small number of subjects (n = 15) who had multiple myeloma; in this study, the authors found that both creatinine clearance and body surface were covariates that impacted lenalidomide's pharmacokinetics …”
mentioning
confidence: 99%
“…19 Recently, the PopPK of lenalidomide was explored in a small number of subjects (n = 15) who had multiple myeloma; in this study, the authors found that both creatinine clearance and body surface were covariates that impacted lenalidomide's pharmacokinetics. 20 However, PK differences appeared to exist between HVs and patients for oral immunomodulatory drugs. Plasma exposure (AUC) to lenalidomide has been shown to be higher in patients than in HVs, even when renal function was comparable.…”
mentioning
confidence: 99%